Genetic characteristics and pathogenesis of clade 2.3.4.4b H5N1 high pathogenicity avian influenza virus isolated from poultry in South Korea, 2022–2023 - Ra Mi Cha; Min-Ji Park; Yoon-Gi Baek; Yu-Na Lee; Yunyueng Jang; Yong-Myung Kang; Gyeong-Beom Heo; Se-Hee An; Kwang-Nyeong Lee; Jae-Kyeom Kim; Hye-Ryoung Kim; Youn-Jeong Lee; et al. (Virus Research)
During the 2022–2023 winter season in South Korea, a novel clade 2.3.4.4b H5N1 HPAIV was first detected in wild birds, which then subsequently caused multiple outbreaks in poultry farms and wild birds. This study aimed to investigate the genetic characteristics of H5N1 HPAIVs isolated during the 2022–2023, along with their pathogenicity and transmissibility in chickens and ducks. The clade 2.3.4.4b H5N1 HPAIV viruses caused outbreaks in 75 poultry farms and detected in 174 wild bird cases. Phylogenetic analysis of hemagglutinin genes revealed that the South Korean H5N1 HPAIV isolates were closely related to Eurasian and American HPAIVs isolated between 2022 and 2023. In total, 21 diverse genotypes (22G0–22G20) were identified in virus isolates from poultry and wild birds, among which 22G7 was the dominant genotype. The 22G1 genotype (A/duck/Korea/H493/2022(H5N1)) caused high virulence and pathogenicity, with a 100 % mortality rate in specific-pathogen-free chickens. Ducks inoculated with genotypes 22G1 or 22G7 (A/duck/Korea/H537/2022(H5N1)) showed neurological signs, with 60 %–80 % mortality rate. In the contact groups of ducks, 100 % of transmissibility was observed. Notably, in the 22G7-inoculated group, viral shedding via the cloacal route was longer, and viral replication in the cecal tonsil was higher than that in the 22G1-inoculated group, which may have contributed to the dominancy of the 22G7 genotype. Therefore, better understanding of the genetic and pathogenic features of HPAI viruses is important for effective virus control in the field.